2023
DOI: 10.7759/cureus.48095
|View full text |Cite
|
Sign up to set email alerts
|

Exploring YouTube Videos About Anorexia Nervosa on the Basis of Reliability, Popularity, and Contributions of Healthcare Professionals: A Cross-Sectional Study

Ananthakrishnan Suresh,
Lalitha Lalithya Pallempati,
Palak Saxena
et al.

Abstract: Background: Anorexia nervosa, an eating disorder, is characterized by a distorted body image, intense fear of gaining weight, and self-imposed starvation. The aim of this study is to analyze type of information as well as its quality and reliability on YouTube about anorexia nervosa.Methodology: A cross-sectional observational study was conducted on 59 Youtube videos using anorexia nervosa-related keywords in June 2023. The characteristics of the YouTube videos, such as the language of the information, the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…We included 71 videos, of which 64% were uploaded over a year ago and were not updated. Suresh et al also had a similar finding, wherein around 71.2% of the videos they analyzed were uploaded more than a year ago [13]. In our study, the cumulative number of views on these videos was 14,532,527, similar to the finding in the study conducted by Kunze et al, who analyzed 50 videos and reported 14,141,285 views [17].…”
Section: Discussionsupporting
confidence: 90%
“…We included 71 videos, of which 64% were uploaded over a year ago and were not updated. Suresh et al also had a similar finding, wherein around 71.2% of the videos they analyzed were uploaded more than a year ago [13]. In our study, the cumulative number of views on these videos was 14,532,527, similar to the finding in the study conducted by Kunze et al, who analyzed 50 videos and reported 14,141,285 views [17].…”
Section: Discussionsupporting
confidence: 90%
“…The quality and reliability of the sample videos were objectively evaluated using the GQS and the Reliability Score (derived from the DISCERN tool for assessment of written health information) respectively. Suresh et al and Dobosz et al conducted comparable analyses regarding anorexia nervosa and body dysmorphic disorder respectively, to evaluate the standard and utility of the information published online [2,15]. The results were found to be statistically significant only about the quality of the videos measured by GQS.…”
Section: Discussionmentioning
confidence: 99%
“…YouTube, a widely used American social media platform for video sharing, plays a significant role in this context. Users leverage YouTube for a variety of purposes, including the dissemination of health-related information [2]. However, the abundance of information that may or may not be false makes it difficult for individuals to find trustworthy sources of information, as observed in the coronavirus disease 2019 (COVID-19) pandemic.…”
Section: Introductionmentioning
confidence: 99%